Mos geometricus v. Reality: Quantity, Quality, Time and Information in Combat Simulations since the Middle Ages - Gassmann Jürg; Gassmann Samuel (Acta Periodica Duellatorum)
The non-lethal simulated training of lethal reality, whether it be single combat or war, was historically a question of life and death.